Syed Ahmad Khan's Twin Objectives of Educational Reforms in British India: Muslim Advancement and Hindu-Muslim Unity - Md Yousuf Ali; Osman Bakar (International Islamic University Malaysia (IIUM), 2024)
Indexed by ERA/MyCite